Tipe Pola Asuh Orang tua Dengan Anak Temper Tantrum Di Di SDI Al-Huda Kota Kediri - Beti Malia Rahma Hidayati; Roudhotul Janah (Universitas Islam Tribakti Lirboyo Kediri, 2021)
Parents have an important role in the development of children, especially emotional development. Often parents are tested for the presence of emotional disorders of the child. For example, explosive emotions are often referred to as temper tantrums. This study aims to find out the type of parenting pattern, temper tantrum behaviour in children, and the influence of parenting patterns on the temper tantrum of children in grade 2 SDI Al-Huda Kediri City. This quantitative study involved 50 subjects. The data was obtained from questionnaires and analyzed using simple linear regression. The results showed that parenting patterns had a significant influence on the child's tantrum temper.